Mesenchymal Stem Cell–Derived Exosomes: A Promising Biological Tool in Nanomedicine - Wei, Wumei; Ao, Qiang; Wang, Xiaohong; Cao, Yue; Liu, Yanying; Zheng, Song Guo; Tian, Xiaohong (Frontiers in Pharmacology, 2021)
As nano-scale biological vesicles, extracellular vesicles (EVs)/exosomes have been studied in the diagnosis, prevention and treatment of many diseases, especially exosomes derived from mesenchymal stem cells (MSC-exosomes). Meanwhile, through the combination of nanotechnology and biotechnology, exosomes have emerged as innovative tools for the development of nanomedicine. This review focuses on a profound summarization of MSC-exosomes as a powerful tool in bionanomedicine. It systemically summarized the role of MSC-exosomes as nanocarrier, drug loading and tissue engineering, and their potential contribution in a series of diseases, as well as the advantages of exosomes over stem cells and synthetic nanoparticles, and potential disadvantages. The in-depth understanding of the functions and mechanisms of exosomes provides insights into the basic research and clinical transformation in the field of nanomedicine.